Probing the Pre-diagnostic Phase of Parkinson's Disease in Population-Based Studies - Dommershuijsen, Lisanne J.; Boon, Agnita J. W.; Ikram, M. Kamran (Frontiers in Neurology, 2021)
Parkinson’s disease covers a wide spectrum of symptoms, ranging from early non-motor symptoms to the characteristic bradykinesia, tremor and rigidity. Although differences in the symptomatology of Parkinson’s disease are increasingly recognized, there is still a lack of insight into the heterogeneity of the prediagnostic phase of Parkinson’s disease. In this perspective, we highlight three aspects regarding the role of population-based studies in providing new insights into the heterogeneity of prediagnostic Parkinson’s disease. First, we describe some specific advantages of population-based cohort studies, including the design which overcomes some common biases, the broad data collection and the high external validity. Second, we draw a parallel with the field of Alzheimer’s disease to provide future directions to uncover the heterogeneity of prediagnostic Parkinson’s disease. Finally, we anticipate on the emergence of prevention and disease-modification trials and the potential role of population-based studies herein. In the coming years, bridging gaps between study designs will be essential to make vital advances in elucidating the heterogeneity of prediagnostic Parkinson’s disease.